Oncologic outcomes and associated factors of colon cancer patients aged 70 years and older - Byeo Lee Lim; In Ja Park; Jun-Soo Ro; Young Il Kim; Seok-Byung Lim; Chang Sik Yu (Annals of Coloproctology)
Purpose The aim of this study was to examine the prognosis and associated risk factors, including adjuvant chemotherapy (CTx), in elderly patients with colon cancer. Methods This retrospective study included patients who underwent radical resection for colon cancer between January 2010 and December 2014 at Asan Medical Center. The effects of stage, risk factors, and chemotherapy on overall survival (OS) and recurrence-free survival (RFS) were compared in patients aged ≥70 and <70 years. Results Of 3,313 patients, 933 (28.1%) was aged ≥70 years. Of the 1,921 patients indicated for adjuvant CTx, 1,294 of 1,395 patients (92.8%) aged <70 years and 369 of 526 patients (70.2%) aged ≥70 years received adjuvant CTx. Old age (≥70 years) was independently associated with RFS in overall cohort. Among patients aged ≥70 years indicated for adjuvant CTx, the 5-year OS (81.6% vs. 50.4%, P<0.001) and RFS (82.9% vs. 67.4%, P=0.025) rates were significantly higher in those who did than did not receive adjuvant CTx. Additionally, adjuvant CTx was confirmed as an independent risk factor of both OS and RFS in patients aged ≥70 years indicated for adjuvant CTx. Conclusion Old age was associated with poor RFS and adjuvant CTx had benefits in OS as well as RFS in elderly patients eligible for adjuvant CTx.